Algal Biomolecules in Cardiovascular Disease: A Review of Current Evidence and Emerging Therapeutic Avenues - Sunil N. Thitame; Ashwini A. Aher (Journal of Pharmacy and Bioallied Sciences)
This devastating noncommunicable condition, commonly referred to as Cardiometabolic disease, continues to be a public health issue of significant global burden with high mortality rates. The contemporary studies are, therefore, aimed at such nutritional approaches, and among the natural products with cardiovascular potential, algae seem to be particularly promising. Micro and Macro algae namely green, red, and brown alga contain PUFA, antioxidants, peptides, and polysaccharides, which have CPD protection effects. This review aims to identify the role algae play in cardiovascular diseases due to their impact on lipid profile, blood pressure, and inflammation, together with antioxidant effects. In addition, the protective effects on cardiovascular diseases by algae are also described, as well as the mechanisms of action involved. The study’s conclusions indicate that algae might act as at least a supplementary or, potentially, an alternative approach in CVD treatment, even though additional clinical trials are required to determine its effectiveness.